ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA PADA MATERI BANGUN RUANG SISI DATAR DILIHAT DARI GENDER - Widyastuti, Anggi Citra; Permana, Dicky; Sari, Indah Puspita (IKIP Siliwangi, 2018)
The aim of the research is to analyze the quality of mathematical creative thinking ability based on the students' gender by giving 4 items of written test covering 4 indicators, namely fluency, flexibility, originality, and elaboration. The subjects were 32 students consisting of 16 male students and 16 female students in SMP Negeri 8 Cimahi. The type of research used is qualitative descriptive. Sampling in this research using purposive sampling technique (sample aims). Conclusion from the results and discussion that the ability of mathematical creative thinking of male students is better than female students in solving mathematical problems on the matter of building a flat side room